PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL DAN GREEN ACCOUNTING TERHADAP NILAI PERUSAHAAN - Indri Ramadhayani; Dian Widiyati (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine how the influence of Financial Performance, Capital Structure and Green Accounting on Firm Value. This type of research uses associative quantitative, the object of research is pharmaceutical companies listed on the Indonesia Stock Exchange in 2018-2022, using purposive sampling method in collecting data samples and the type of data used is secondary data. The total population in this study were 12 companies and the total sample of 10 companies so that 50 observation data were obtained in this study. Analysis of the data used in this study using panel data regression using the Eviews 12 Software. The results of the study indicate that Financial Performance, Capital Structure and Green Accounting simultaneously have an effect on Firm Value, Financial Performance has no effect on Firm Value, Capital Structure has an effect on Firm Value and Green Accounting has no effect on Firm Value.